Process of organizational problem definition: how to evaluate and how to improve - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2003)
Managerial problem solvers need to be able to evaluate the effectiveness of their efforts in making sure that they are attending the right problem. They also need to know of some specific steps they can take, when necessary, to improve the effectiveness of this process of problem definition. This paper discusses modeling a measuring instrument to evaluate problem definitions, based on which it empirically compares two methods for helping to define problems in organizations. And, in light of the results of this comparison, it proposes a synthesis method designed by combining the strengths of these two methods of problem definition. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: ill-structured problem solving; problem structuring; problem formulation; problem definition; purposes; PROBLEM FORMULATION; MODEL; KNOWLEDGE; STYLES; GUIDE; AIDS; MESS